The Role of Agents in Increasing Sharia Insurance Customers at PT. Askrida Syariah Insurance Medan Branch - Aida Malan Sari; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the role of agents in increasing insurance customers at PT Asuransi Askrida Syariah Medan Branch . Agents play an important role in offering products that exist in sharia insurance companies, where agents provide services in offering protection services for the financial needs of both individuals and groups, both health needs and those related to property. The methods in this study are the type of research, the nature of the research, the research approach, data collection, and data analysis. The results of this study are agents have a very important role in increasing sharia insurance customers, namely an agent plays a role in expanding the market, especially for people who have not used insurance services through direct socialization, agents also play a role in maintaining and improving the existing market by trying to always maintain communication with customers in order to provide the best service. In addition, agents also play a role in carrying out activities to the community by introducing financial planning and risk management in insurance and an agent also plays a role in selecting risks for prospective customers by identifying the possibility of risks faced by potential customers, evaluating, and measuring the magnitude of the risk. risks that may occur and determine the best method to deal with the identified risks.